Behavior Classification Physical/Chemistry PA66/HCl Binary System Utilized to Obtain Separation Membranes (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: polymer-low molecular liquid systems; true solution; PA66/HC binary system